2009
DOI: 10.5507/fot.2009.035
|View full text |Cite
|
Sign up to set email alerts
|

The structure and species richness of the diatom assemblages of the Western Carpathian spring fens along the gradient of mineral richness.

Abstract: Species composition changes along the pH and calcium gradients within wetlands were frequently studied for different groups of organisms, but few data are available for algae. Here we list 188 diatom taxa collected as epibryon and epipelon at 13 spring fens in the Western Carpathians distributed along the gradient of mineral richness. Species richness decreased along the gradient from calcareous fens to mineral-poor Sphagnum-fens. In agreement with fen typology based on higher plants, bryophytes, and molluscs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 34 publications
(24 reference statements)
8
37
0
Order By: Relevance
“…Cantonati & Spitale (2009) and Cantonati et al (2012b) made similar observations in a few iron-rich springs, but this was not an apparent feature here. Fránková et al (2009) observed poor valve silicification in petrifying springs, concurring with somewhat lower silica concentrations than in less mineral-rich fens. The solubility of biogenic silica increases markedly at pH > 8.5 and such values may develop in carbonate-precipitating biofilms (Bisset 2008).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Cantonati & Spitale (2009) and Cantonati et al (2012b) made similar observations in a few iron-rich springs, but this was not an apparent feature here. Fránková et al (2009) observed poor valve silicification in petrifying springs, concurring with somewhat lower silica concentrations than in less mineral-rich fens. The solubility of biogenic silica increases markedly at pH > 8.5 and such values may develop in carbonate-precipitating biofilms (Bisset 2008).…”
Section: Discussionsupporting
confidence: 53%
“…Seventeen Swiss springs, also presenting a wider conduc- tivity range and no obvious signs of pollution, yielded only 136 taxa (Taxböck & Preisig 2007) and 197 taxa were noted in 52 samples from 27 Austrian springs and spring streams (Gesierich & Kofler 2010). Thirteen springs in the Western Carpathians yielded 188 taxa, with 114 occurring in calcareous fens (Fránková et al 2009). Werum & Lange-Bertalot (2004) examined 97 springs from regions with varying geology in SWGermany (Hessen) but recorded only one hundred taxa more than the 300+ tallied here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Europe, Chamaepinnularia schauppiana lange-Bertalot et metzeltin was noted to occur in oligo-dystrophic waters in Finland but also in mire and fen pools (cantonati & lange-Bertalot 2009). It was also observed that several other species occurred in Europe both in low pH lakes (kapetanoVić et al 2011) and in mountain fens with a high concentration of minerals (FránkoVá et al 2009). Chamaepinnularia krookiformis was noted to occur in the area of Poland both in seawaters and saline inland waters in the coastal zone (WitkoWski 1994;WitkoWski et al 2000;Bąk et al 2006), in freshwater ecosystem such as upland rivers (Wojtal 2009;peszek et al 2015), quaternary springs located near Łódź (Żelazna-Wieczorek 2011), and in athalassic habitats in Central Poland (Żelazna-Wieczorek et al 2015).…”
Section: Introductionmentioning
confidence: 97%